Um modelo de interface extensível para sistemas de registro eletrônico de saúde baseados na norma ISO 13606 - Elisa Tuler de Albergaria (2016)
The relevance of health care of people has boosted the creation, management and analysis of health data recently. Data derived from health care are inherently diverse and, in most cases, are spread in the various health facilities in which a particular person receives care throughout life. In an ideal scenario, such health data, as long as preserved the right of personal confidentiality and privacy, should be shared by the different health facilities. Aiming to enhance this exchange of clinical histories, at different levels of care, a novel concept has arisen: the Electronic Health Record (EHR). Electronic Health Record systems propose that events in multiple health organizations should be stored and shared, providing patient`s information in an integrated manner. There are different standards to guide the development of electronic health systems that allow the exchange of health data. This work focuses on the ISO 13606 standard, which proposes a dual model architecture: the knowledge/information levels (ISO/CEN 13606). The goal of this standard is to separate the modeling of clinical concepts from the data model. At this way, systems may become more flexible, able to cope with the complexity of health models and more resilient to conceptual changes in the domain. However, health professionals struggle to handle such systems, since they usually requires advanced technical knowledge about computers and the adopted standards. Thus, in this work, we propose a model of interaction for end-users (i.e., health professionals) that allow them to customize EHR interfaces while keeping the structure and standardization of data in accordance with the ISO 13606. Based on the Design Science Research method, we created, developed and evaluated an extensible interface model based on the ISO 13606 standard to guide the development of EHR. The model aims to provide three essential properties of these systems: flexibility in conceptual modeling; ease of interaction; and standardization and structuring of data. The proposed model is based on the theory of Semiotics Engineering, which considers the user-system interaction as a process of communication between the system designer and end-users. The model has elements in its architecture to consider this aspect and allows specialists to become co-authors of the system. Initial prototype evaluations were carried out in order to analyze its feasibility and usefulness in real scenarios. The indicators obtained in the evaluations were positive, bringing benefits to the ability of health professionals to customize the system interface, while keeping the data stored in a standardized and structured manner.